2001
DOI: 10.1211/0022357011778016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cholesterol and model transmembrane proteins on drug partitioning into lipid bilayers as analysed by immobilized-liposome chromatography

Abstract: We have analysed how cholesterol and transmembrane proteins in phospholipid bilayers modulate drug partitioning into the bilayers. For this purpose we determined the chromatographic retention of drugs on liposomes or proteoliposomes entrapped in gel beads. The drug retention per phospholipid amount (the capacity factor Ks) reflects the drug partitioning. Cholesterol in the bilayers decreased the Ks value and hence the partitioning into the membrane in proportion to the cholesterol fraction. On average this cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Several studies (16,(32)(33)(34) revealed a significant decrease of the membrane affinity of a variety of acidic, basic and neutral drugs when Chol was present in phospholipid bilayers. This was assigned to motion restrictions of the fatty acyl chain regions close to the lipid head groups and to the higher rigidity of the membrane induced by Chol in general, leading to an impeded integration of the drug molecules into the lipid bilayer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (16,(32)(33)(34) revealed a significant decrease of the membrane affinity of a variety of acidic, basic and neutral drugs when Chol was present in phospholipid bilayers. This was assigned to motion restrictions of the fatty acyl chain regions close to the lipid head groups and to the higher rigidity of the membrane induced by Chol in general, leading to an impeded integration of the drug molecules into the lipid bilayer.…”
Section: Discussionmentioning
confidence: 99%
“…Sterically stabilized liposomes prepared from phospholipids with covalently attached poly(ethylene glycol) (PEG lipids) are commonly used for the preparation of long based methods for the determination of drug partitioning such as potentiometric [55][56][57], chromatographic [58][59][60][61][62][63][64], electrophoretic [65][66][67] and calorimetric methods [68,69]. From Lundhal and coworkers technique [58,59] liposomes and disks were immobilized in chromatographic gel beads so that the partition of a large set of drugs was quickly and conveniently assessed [54].…”
Section: Bilayer Disks From Lipids and Hydrophilic Polymers Or Polyetmentioning
confidence: 99%
“…Incorporation of higher Chol concentration in liposomal formulations increased the PSC 833 release rate. The planar and rigid ring system of Chol is thought to reside in outer layer part of the fatty acyl chain region where it tends to restrict the motion of chains in liquid crystalline bilayers (55,56) which may increase tendency of PSC 833 to partition in the release medium. We have previously reported phospholipids concentration-dependent drug release from liposomes (28).…”
Section: Discussionmentioning
confidence: 99%